Pacific Rim Objective Measurement Symposium (PROMS) 2016 Conference Proceedings Rasch and the Future (Springer Singapore, 2018)
This book gathers original studies presented at the PROMS 2016 conference on Rasch theories and Rasch-based applications. It provides significant examples used to address practical measurement problems across a range of disciplines, including: Classic Testing Theory (CTT), Item Response Theory (IRT), philosophy of measurement, dimensionality, the role of fit statistics and research, business and industrial applications, health-related research and the latest Rasch-based computer software. PROMS welcomes empirical and theoretical studies and workshops, preferably with an emphasis on the Rasch model. Special attention is paid to manuscripts submitted by non-native English-speaking authors from Pacific Rim countries, regions and beyond. PROMS 2016 (Pacific Rim Objective Measurement Symposium) was held July 30-August 3, 2016 in Xi'an, China. The goal of the conference was to bring together researchers, scholars and professors from research institutes, universities, hospitals, business and management sectors, as well as professional practitioners, to exchange and share ideas, problems and solutions regarding the multifaceted aspects of the Rasch model and on the much debated yet highly topical issues of objective assessment.